Internationalization strategy of quidgest - Abrantes, Sara Fernandes da Costa (2018)
The underlying work project was executed with the purpose of analyze Quidgest’s business and conduct to a strategy of internationalization. In order to do so, an internal analysis was performed with the goal of describing Quidgest as a company, highlighting its values and its business and strategic objectives. Also, a competitive advantage analysis was performed with the objective of determining the competitors and the resources that provide a competitive advantage to Quidgest. Finally, in order to have success in the internationalization plan, the strengths and weaknesses of Quidgest were underlined.